Injectable and Temperature-Sensitive Titanium Carbide-Loaded Hydrogel System for Photothermal Therapy of Breast Cancer - Yao, Jun; Zhu, Chuanda; Peng, Tianjiao; Ma, Qiang; Gao, Shegan (Frontiers in Bioengineering and Biotechnology, 2021)
Recently, organic–inorganic hybrid materials have gained much attention as effective photothermal agents for cancer treatment. In this study, Pluronic F127 hydrogel-coated titanium carbide (Ti3C2) nanoparticles were utilized as an injectable photothermal agent. The advantages of these nanoparticles are their green synthesis and excellent photothermal efficiency. In this system, lasers were mainly used to irradiate Ti3C2 nanoparticles to produce a constant high temperature, which damaged cancer cells. The nanoparticles were found to be stable during storage at low temperatures for at least 2 weeks. The Ti3C2 nanoparticles exhibited a shuttle-shaped structure, and the hydrogels presented a loosely meshed structure. In addition, Ti3C2 nanoparticles did not affect the reversible temperature sensitivity of the gel, and the hydrogel did not affect the photothermal properties of Ti3C2 nanoparticles. The in vitro and in vivo results show that this hydrogel system can effectively inhibit tumor growth upon exposure to near-infrared irradiation with excellent biocompatibility and biosafety. The photothermal agent-embedded hydrogel is a promising photothermal therapeutic strategy for cancer treatment by enhancing the retention in vivo and elevating the local temperature in tumors.